An Autonomous Maintenance Design Based on Overall Resource Effectiveness (ORE) Analysis: A Case Study of Paving Molding Machine - Indira Kusuma Wardani; Fransiskus Tatas Dwi Atmaji; Judi Alhilman (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
The paving molding machine is one of the machines used to produce black paving at PT XYZ. Based on the historical data from the engineering maintenance department, this machine has the highest breakdown frequency which affected the low performance and productivity of the machine. To solve this problem, the effectiveness of the paving molding machine was analyzed using overall resource effectiveness (ORE) methods. ORE aims to analyze machine indicators, consisting of readiness, availability of the facility, changeover efficiency, availability of material, availability of manpower, performance efficiency, and quality rate. The ORE analyzed result shows that values of performance efficiency of paving molding machine were 64.54% and still below the standards of the ORE. To increase the ORE, a design of autonomous maintenance (AM) was proposed. The proposed design means the operator is given the responsibility to maintain the basic condition of the machine to minimize the damage of the paving molding machine at PT XYZ. The result of ORE analysis, especially in the performance efficiency, will be an input for the engineering maintenance department to make an AM basic design that can be executed by each of the machine's operators. In general, this research’s novelty is to combine the application of the ORE method with the AM basic design, whereas the AM is one of the pillars of total productive maintenance (TPM).